Investigation on the credit risk transfer effects on the banking stability and performance - R. Younes (Cogent Economics & Finance, 2022)
Considered among of the main causes of the 2007 financial crisis, the credit risk transfer activities deserve nowadays particular attention. This study discusses the continuous effectiveness of the credit risk transfer activities by investigating their effects on the bank risk, liquidity and profitability before the crisis event and contributes to the recent scarce literature identifying this effect in the post-crisis period. Using models treating this impact on two samples of US commercial banks over the period from 2001 to 2017, the obtained results suggest an overall amplification of the risk incurred by banks notably before the crisis, a decrease of liquid assets hold on balance sheet and, generally an increase of the profitability. The employment of credit derivatives does not exhibit a conclusive result of its impact on the banking stability and performance. Nevertheless, the effect of residential mortgage loans securitization on bank risk appeared to be negative after the crisis, indicating that the securitization of this type of credit can reduce the bank risk in the detriment of a lower profit, in the new regulatory context required by Basel III.
Keywords: G21; G32; G23; 330; Credit risk transfer; securitization; credit derivatives; bank risk; bank liquidity